The various functions of the speech act of "silence" in a literary text - Ismoilova, Zaripa; Axmedova, Nodira; Usmonova, Mohitabon (The Lingua Spectrum, 2025)
In modern linguistics and literary studies, the exploration of various aspects of the speech process – particularly the analysis of the linguistic-pragmatic, semiotic, and aesthetic essence of the phenomenon of silence – has become one of the most relevant scientific directions. Silence is usually regarded as the absence of speech, quietness, or a pause. However, in the context of a literary text, silence is not merely the absence of words; rather, it manifests as an active speech act that replaces words and creates meaning. This annotation analyzes the different functions of the speech act of “silence” in literary texts – communicative, psychological, aesthetic, moral-social, and semiotic. According to the speech act theory proposed by J.L. Austin (1962) and J.R. Searle (1969), any utterance by a speaker not only conveys information but also performs practical actions – illocutionary (intentional), perlocutionary (influential), and locutionary (expressive) acts. From this perspective, silence, too, represents a specific type of speech act: even when a person remains silent, they express an attitude, transmit information, or communicate thoughts in an implicit way.